(untitled) (World Science, 2019)
Vertebral artery syndrome is a collective term that encompasses a number of cerebral, cardiovascular and autonomic syndromes resulting from lesions of the sympathetic plexus of the vertebral artery, deformation of its wall or lumen changes caused by cervical spine disorders. Manual therapy is one of the recognized methods of treatment for the said condition. This study discusses the possibility of applying manual therapy combined with shock wave therapy in cases of vertebral artery syndrome resistant to other methods of treatment.